Life events in late paraphrenia and depression - Fuchs, Thomas (Psychopathology, 1999)
38 patients with late paraphrenia and 38 with endogenous depression of late onset were examined and various premorbid characteristics and biographical data compared. The main objective of the study was to look for differential risk factors and for biographical experiences that suggested a specific premorbid vulnerability in paranoid and depressive patients. In the paranoid group, a significantly higher frequency of discriminating, humiliating or threatening experiences during earlier life was found. These included expulsion from home in the years 1944-46 (53%), somatic handicaps such as amputations (13%), illegitimate birth (11%) or illegitimate children (13%), and others. In the depressed group, severe early loss prevailed (29%). The significance of these results for the etiology of late-life mental disorder is discussed.